Successful treatment of acquired amegakaryocytic thrombocytopenia with eltrombopag and immunosuppressant. (18th August 2022) - Tian, Hong; Kong, Danqing; Li, Yun; Gu, Chengyuan; Yu, Ziqiang; Wang, Zhaoyue; Wu, Depei; Yin, Jie
Abstract: Acquired amegakaryocytic thrombocypenia (AAMT) is an extremely rare hematologic disorder and standard treatment strategy has not been established. We described herein two cases of AAMT who were fully responded to eltrombopag and immunosuppressant. Patient 1 was refractory to steroid, IVIG and recombinant human thrombopoietin (rhTPO). Patient 2 did not respond to high dosage of steroid, IVIG, rhTPO and rituximab. Moreover, his AAMT progressed to aplastic anemia in 5 months. Both patients took eltrombopag and immunosuppressant, then they achieved long-term remission without obvious side effects. Our findings suggest that this combination can be a valuable alternative in AAMT.